2019
DOI: 10.1021/acs.est.8b06305
|View full text |Cite
|
Sign up to set email alerts
|

Natural Chlordecone Degradation Revealed by Numerous Transformation Products Characterized in Key French West Indies Environmental Compartments

Abstract: Production and use of the insecticide chlordecone has caused long-term environmental pollution in the James River area and the French West Indies (FWI) that has resulted in acute human-health problems and a social crisis. High levels of chlordecone in FWI soils, even after its ban decades ago, and the absence of detection of transformation products (TPs), have suggested that chlordecone is virtually nonbiodegradable in the environment. Here, we investigated laboratory biodegradation, consisting of bacterial li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 50 publications
8
59
0
Order By: Relevance
“…In this study we relied on exact masses, unique isotope distribution patterns, and retention times to support the indentity of metabolites classes, namely hydrochlordecones, polychloroindenes, and carboxylated polychloroindenes with varying numbers of chlorine substituents. The consistency of the results with previous reports [24,33] and highly characteristic chlorine isotope pattern leave little doubt to the structure of the compounds, other than the actual position of substituents on the rings. Only purification of each compound and NMR could resolve such structural details, and these are beyond the scope of this work, and not necessary to evaluate extent of dechlorination.…”
Section: Detection Of Cld Metabolites Using Best Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…In this study we relied on exact masses, unique isotope distribution patterns, and retention times to support the indentity of metabolites classes, namely hydrochlordecones, polychloroindenes, and carboxylated polychloroindenes with varying numbers of chlorine substituents. The consistency of the results with previous reports [24,33] and highly characteristic chlorine isotope pattern leave little doubt to the structure of the compounds, other than the actual position of substituents on the rings. Only purification of each compound and NMR could resolve such structural details, and these are beyond the scope of this work, and not necessary to evaluate extent of dechlorination.…”
Section: Detection Of Cld Metabolites Using Best Methodssupporting
confidence: 88%
“…The genome of the Citrobacter strain in these studies contained no reductive dehalogenase genes and thus transformation was likely cometabolic [32]. A very recent paper by the same team further identified and characterized many chlordecone transformation products [33], using chemical reduction, organic synthesis, and Nuclear magnetic resonance (NMR) spectroscopy NMR to elucidate isomer structures. Significantly, they further detected and quantified some of these same transformation products in soil samples from Martinique.…”
Section: Introductionmentioning
confidence: 99%
“…5, Fig. S5) were processed to recover a hierarchical clustering of environmental samples according to their taxonomic composition 6 . It was noticed that sulfate-reducing bacteria were much more present in bed sediments than in the other compartments, as previously reported [30][31][32] .…”
Section: Investigation Of the Incubation Conditions Leading To Bactermentioning
confidence: 99%
“…More recently, two bacterial consortia (86 and 92), isolated from microbial enrichment cultures from chlordecone-contaminated soils and wastewater treatment plant sludge, were able to transform chlordecone, under anoxic conditions, at room temperature. Several TPs were identified and grouped into three families: hydrochlordecones (family A), polychloroindenes (family B) and polychloroindenecarboxylic acids (family C) 5,6 . TPs from families B and C that were predominant arose from a ring-opening dechlorination of the chlordecone bishomocubane cage.…”
mentioning
confidence: 99%
“…However, a few years ago, Macarie and coworkers (Macarie et al 2016) show that there are no thermodynamic reasons for limiting the CLD degradation. Recently, Chevallier et al (2019) also found metabolites of CLD (dechlorinated CLD derivatives with loss of up to 7 Cl) in Caribbean soils. They also show that microorganisms, susceptible to degrade CLD, are present in the Caribbean soils demonstrating that natural biodegradation should be possible.…”
Section: Introductionmentioning
confidence: 99%